تأثير إضافة بعض المخلفات العضوية والكبريت الزراعي في استجابة الشعير للتسميد الفوسفاتي في تربة من منطقة سهل الروج - خورشيد, عبد الغني; ترت, محمد (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في البيت الزجاجي التابع لكلية الزراعة للموسم الزراعي 2007/2008 على تربة أخذت من منطقة سهل الروج (محافظة ادلب) وذلك لزراعة الشعير صنف (فرات 1) في أصص بلاستيكية سعة الأص الواحد 18 كغ تربة وبثلاثة مكررات وفق معاملات التجربة التي استخدمت فيها المخلفات العضوية (الدواجن، الأبقار، الأغنام) بمعدل 15 طن / هكتار، واستخدم الكبريت الزراعي كذلك بمعدل 2 طن / هكتار، كما شملت المعاملات نوعين من الأسمدة الفوسفاتية وهي سماد السوبر فوسفات (46 % P2O5) بمعدل 80 كغ / هكتار، ومسحوق الصخر الفوسفاتي (23 % P2O5) بمعدل 160 كغ / هكتار. صممت التجربة بطريقة القطاعات العشوائية الكاملة (CRBD) وبنهاية التجربة تم حساب حاصل الحبوب لكل معاملة وما تحتويه الحبوب من الفوسفور. أظهرت النتائج أن إضافة المخلفات العضوية والسماد الفوسفاتي والكبريت الزراعي أدى إلى زيادة إنتاجية الشعير مقارنة مع الشاهد وإلى زيادة محتوى الحبوب من الفوسفور، إلا أن التداخل بين هذه المعاملات وإضافة المخلفات العضوية وخاصة مخلفات الدواجن مع سماد السوبرفوسفات الثلاثي حقق زيادة في الإنتاج بنسبة 50 % تقريباً، وزيادة في محتوى الحبوب من الفوسفور حتى 65 % وتفوقت أيضاً هذه المعاملة على المعاملات جميعاً. This research has been carried out in the greenhouse of the Faculty of Agriculture, of the agricultural season 2007/2008 on the soil taken from Al-Rouge plain region of (Idleb) for barley cultivation class (Furat 1) in plastic pots capacity 18 kg soil with three replicates, according to the experiment treatments which use organic waste (poultry, cattle and sheep) at 15 tons/ha. Agricultural sulfur was also used at the rate of 2 tons/ha, and coefficients included two types of phosphate fertilizers: Super phosphate fertilizer (46 % P2O5) at 80 kg/ha and phosphate rock powder (23 % P2O5) at 160 kg/ha. The experiment was designed by (CRBD). At the end of the experiment the yield and grains content of phosphorus were calculated for each treatment. The results show that the addition of organic waste and phosphate fertilizer and agricultural sulfur led to increased productivity of barley, compared with the control, and to the increase of the cereal content of phosphorus, but the overlap between these coefficients and the addition of organic waste, particularly poultry waste with fertilizer super phosphate achieved an increase in production for about 50 % and an increase in cereal contents of phosphorus to 65 % and this treatment also topped all coefficients.